Cement-associated thrombotic embolism in the inferior vena cava and bilateral iliac veins after percutaneous vertebroplasty: a case report. Issue 9 (September 2021) - Hu, Yunxiang; Wang, Yufei; Yu, Zhimin; Li, Xinxian
Percutaneous vertebroplasty (PVP) was first reported in 1987 for treating vertebral hemangiomas. PVP is also an effective treatment for osteoporotic vertebral compression fracture that mainly involves a percutaneous injection of polymethylmethacrylate. Severe complications of PVP have been reported in recent years. However, to the best of our knowledge, cement-associated thrombotic embolism in the inferior vena cava and bilateral iliac veins after PVP has rarely been reported. We experienced a patient with cement-associated thrombotic embolism in the inferior vena cava and bilateral iliac veins after PVP. Fortunately, after conservative therapy, we achieved a satisfactory result. Unfortunately, we could not explain the cause of the cement leakage and formation of the thrombotic embolism. We believe that surgeons should have a better understanding of the fracture pattern and anatomy of the vertebral venous net system. They should also perform meticulous imaging monitoring with slower pushing of the cement to minimize the risks during the PVP. This case report highlights a rare, but potentially life-threatening, complication of PVP. Surgeons need to be aware of the possibility of cement leakage and the formation of cement-associated thrombotic embolism so that they are much more vigilant when performing PVP.